CONTEMPORARY ISSUES IN MIXED MARRIAGES: AN ISLAMIC LEGAL ANALYSIS OF LINGUISTIC ISSUES IN MARRIAGE CONTRACTS - Wahyu Aji Pratama; M. Saeful Amri (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2025)
Purpose - This study examines the legal validity of Indonesian-Taiwanese mixed marriage contracts from an Islamic law perspective, specifically analyzing the impact of linguistic barriers in Ījāb Qabūl on fulfilling the requirements of tarāḍī (consent) and fahm al-'aqd (contract comprehension). This study fills a gap in contemporary Islamic jurisprudence studies regarding the legal implications of language barriers in marriage rituals that potentially affect contract validity. Method - This study employs an empirical juridical method integrated with a socio-legal approach, focusing on KUA Paguyangan, which handles Indonesian-Taiwanese mixed marriage cases with significant linguistic challenges. Primary data were collected through in-depth interviews with KUA officials, field observations of ceremony documentation, and analyses of official marriage records. Findings - This study reveals that cross-cultural Islamic marriages achieve validity through four key elements: linguistic innovation where Taiwanese grooms use native script with Indonesian vocalization (ḥifẓ al-ma'nā ma'a taghyīr al-rasm), legal framework fulfilling comprehension, pronunciation, witness validation, and willingness requirements, institutional adaptation by KUA officials balancing authenticity with accessibility, and theological alignment with Islamic principles of ease (taysīr), concession (rukhṣah), and public interest (maṣlaḥah). Research limitations - The research is limited to one case at KUA Paguyangan; thus, generalization requires caution. However, post-marriage aspects and cultural integration dynamics have not been explored. Originality/value - This research makes an original contribution to the study of Islamic family law in a global context by providing an in-depth analysis of practical solutions to overcome language barriers in religious rituals, which have not received adequate attention in previous academic literature.